Droplet and Microchamber‐Based Digital Loop‐Mediated Isothermal Amplification (dLAMP). Issue 9 (3rd January 2020) - Yuan, Hao; Chao, Youchuang; Shum, Ho Cheung
Abstract: Digital loop‐mediated isothermal amplification (dLAMP) refers to compartmentalizing nucleic acids and LAMP reagents into a large number of individual partitions, such as microchambers and droplets. This compartmentalization enables dLAMP to be an excellent platform to quantify the absolute number of the target nucleic acids. Owing to its low requirement for instrumentation complexity, high specificity, and strong tolerance to inhibitors in the nucleic acid samples, dLAMP has been recognized as a simple and accurate technique to quantify pathogenic nucleic acid. Herein, the general process of dLAMP techniques is summarized, the current dLAMP techniques are categorized, and a comprehensive discussion on different types of dLAMP techniques is presented. Also, the challenges of the current dLAMP are illustrated together with the possible strategies to address these challenges. In the end, the future directions of the dLAMP developments, including multitarget detection, multisample detection, and processing nucleic acid extraction are outlined. With recently significant advances in dLAMP, this technology has the potential to see more widespread use beyond the laboratory in the future. Abstract : Herein, the concept of digital loop mediated isothermal amplification (dLAMP), which allows quantification of the absolute number of nucleic acids, is presented. The current dLAMP techniques, including their advantages and disadvantages are summarized. Furthermore, the challenges faced when applying dLAMP are discussed together with their potential solutions, followed by an outline of their future developments.